Chromatin mutations in pediatric high grade gliomas - Voon, Hsiao P. J.; Wong, Lee H. (Frontiers in Oncology, 2023)
Paediatric high grade gliomas (HGG) are lethal tumours which are currently untreatable. A number of recent studies have provided much needed insights into the mutations and mechanisms which drive oncogenesis in paediatric HGGs. It is now clear that mutations in chromatin proteins, particularly H3.3 and its associated chaperone complex (ATRX), are a hallmark feature of paediatric HGGs. We review the current literature on the normal roles of the ATRX/H3.3 complex and how these functions are disrupted by oncogenic mutations. We discuss the current clinical trials and pre-clinical models that target chromatin and DNA, and how these agents fit into the ATRX/H3.3 mutation model. As chromatin mutations are a relatively new discovery in paediatric HGGs, developing clear mechanistic insights are a key step to improving therapies for these tumours.